Institutions and Behavior: Experimental Evidence on the Effects of Democracy - Bó, Pedro Dal; Foster, Andrew; Putterman, Louis (American Economic Review, 2010)
A novel experiment is used to show that the effect of a policy on the level of cooperation is greater when it is chosen democratically by the subjects than when it is exogenously imposed. In contrast to the previous literature, our experimental design allows us to control for selection effects (e.g. those who choose the policy may be affected differently by it). Our finding implies that democratic institutions may affect behavior directly in addition to having effects through the choice of policies. Our findings have implications for the generalizability of the results of randomized policy interventions.